Islamic Religious Education for Mental Well-Being: Strengthening Students’ Psychological Resilience through Spiritual-Based Learning - Najeeb Yahya; Mowafg Masuwd; Helene Knudstad; Md. Sultan Mahmud (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Mental health challenges among adolescents have increased considerably due to academic pressure, technological changes, and social uncertainty. Islamic Religious Education has substantial potential to contribute to students’ psychological well-being by fostering spirituality, emotional regulation, and resilience. This study aims to examine the effectiveness of spiritual-based Islamic learning in strengthening students’ mental well-being. A mixed-method research design involving 274 senior high school students was conducted. Quantitative data were obtained using standardized resilience, emotional well-being, and spiritual intelligence scales, while qualitative data were collected through interviews and reflective journals. The findings demonstrate that integrating reflective Qur’anic learning, gratitude practices, dhikr, collaborative discussions, and positive psychology significantly improves students’ resilience, emotional stability, optimism, and stress management abilities. Furthermore, students develop stronger self-awareness and healthier coping strategies for academic and social challenges. The novelty of this study is the development of a Spiritual Well-Being Learning Model, integrating Islamic spirituality with positive psychology to enhance holistic student development in Islamic Religious Education